التكافؤ والتوطين والتغريب في الترجمة الإنجليزية للروايات العربية المعاصرة: عمارة يعقوبيان بقلم علاء الأسواني أنموذجاًThe Equivalence, Domestication and Foreignization in the English Translation of the Contemporary Arabic Novels: The Yacoubian Building by Alaa Al-Aswany as a Specimen (Al-Qamar, 2021)
It is usually believed that the translation is just a lingual transformation between two different languages but that is a wrong perception because translation plays the role of a lingual, literary and cultural bridge, at the same time, between the diverse human languages. While this reality has been acknowledged now and several linguists and translators have contributed to the development of this concept since the mid-20th century. The translation studies specialize in the same field and its borders have expanded now to a number of other related and overlapping fields of knowledge. As far as the Equivalence, Domestication and Foreignization are concerned; these are considered among the most preferred strategies for translation between two languages belonging to two totally different civilizations. The translation of contemporary Arabic novels into other languages especially the English language has attracted much attraction during the last few decades, while the Egyptian writer Alaa Al-Aswany is one of those contemporary Arab novel writers whose popularity has reached the non-Arab countries and especially the English-speaking countries of the world because most of his novels have been translated into the English. Especially, The Yacoubian Building is considered among the best sellers in the world that was translated by Humphrey Davies, the British translator, in 2004. The following lines would elaborate traits of the equivalence, domestication and foreignization prevailing over the English translation of the said famous Arabic novel and that would be done through the morphological and semantic analysis of the examples selected from the source and target texts.
Keywords: Equivalence; Domestication; Foreignization; The Yacoubian Building